Effects Different Human Chorionic Gonadotropine Doses for Gonads Maturity Gray Eeltailed Catfish (Plotosus canius) - Wiwin Kusuma Atmaja Putra; Wenti Anggaraini; Tengku Said Raza’i; Tri Yulianto (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2020)
This study aimed to determine the optimum dose of hCGto support the processing gonadal maturation of Gray Eeltailed Catfish (Plotosus canius) and to determine influencing of hCG injections treatment (quality and quantity) to TKG of Gray Eeltailed Catfish (Plotosus canius). The study was conducted in October-November 2018 in Madong, Tanjungpinang City, Riau Island. This study used a completely randomized design (RAL) method with 4 treatments that were control (NaCl), A (dose 15 IU.Kg-1), B (dose 20 IU.Kg-1), and C (dose 25 IU.Kg-1) and 3 replications. Floating net cages (KJA) with size 1mx1mx1m as containers were used to maintain test fish. The results showed that treatment B gave the best results in the study. Treatment B namely injecting hCG with a dose of 20 IU.Kg-1 to reach TKG II for the whole parent, then GSI reached 0.29%, but the HSI value of A treatment was better on 1.93%, egg diameter 1.57 mm, fecundity reached 3,706 grains, with specific growth reaching 0.83 g and histologically, the gonads were characterized by the potential for a fused nucleus and filled with egg yolk and the development of the oocyte only appears smaller and more uniform in diameter. Keyword: oocyte, female, diameter, fecundity, histology